Implementation of Hazard Identification, Risk Assessment, and Determining Control (Hiradc) System for Hazard Risk Management in Mining Work Environment at PT XYZ - Sadewa; Hafid Syaifullah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The mining industry is known as a high-risk sector, which often faces challenges in identifying the causes of work accidents. This research focuses on the implementation of the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) system at PT XYZ, especially at the gold mine. The aim of this research is to improve work safety through hazard identification and effective risk management. The method used includes observation and descriptive analysis of secondary data from the Occupational Health and Safety (K3) department. The research results show that there are 9 potential dangers, with 6 of them in the extreme risk category and the other three in the high category. Through the implementation of the 50 proposed control measures, the risk level was successfully reduced to a safer category. These findings emphasize the importance of implementing HIRADC to reduce work accidents and support operational sustainability in the mining industry.